2022
DOI: 10.1111/ctr.14574
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of deceased donor proteinuria for kidney transplantation: A comprehensive national cohort study

Abstract: Purpose: Proteinuria is frequent in patients with nephropathies and associated with progressive kidney disease and risk for end stage kidney disease. However, the relevance of deceased donor proteinuria on transplant outcome remains uncertain. In this nationwide cohort study, we evaluated the prevalence of proteinuria in deceased donor candidates and measured the impact on outcome after kidney transplantation. Methods: Data from the Swiss Organ Allocation System and the Swiss TransplantCohort Study were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…This study established that within a 36 months post-transplant follow-up period, DP was not associated with impaired patient or graft survival or impaired graft function. Our results affirm the previous findings of Kuhn et al [ 8 ], who demonstrated that there was no effect of DP in KTX on graft survival or function within 12 months after surgery [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study established that within a 36 months post-transplant follow-up period, DP was not associated with impaired patient or graft survival or impaired graft function. Our results affirm the previous findings of Kuhn et al [ 8 ], who demonstrated that there was no effect of DP in KTX on graft survival or function within 12 months after surgery [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of proteinuria in kidney transplant recipients ranges from 7.5% to 45% [ 7 ]. However, proteinuria is much more prevalent in organ donors, with low- and high-grade proteinuria occurring in 35.1% and 74.1% of allocated kidneys, respectively [ 8 ]. Yet, there are no official guidelines regarding donor proteinuria (DP) in kidney allocation, and the long-term impact of DP as an independent risk factor has not yet been validated.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, a national cohort study in Switzerland, which had a smaller sample size but longer follow-up than ours, found no association between deceased donor proteinuria, defined as uPCR >30mg/mmol, and graft survival or function. 26 Our findings add to the literature by showing consistent results in an adequately powered study that includes more DCD transplants, using a biomarker that is more widely reported at the time of donor assessment. In the subgroup of donors with uPCR recorded, we found consistent results despite applying a higher threshold (≥100 mg/mmol), although low numbers and potential selection bias limit interpretation of this result.…”
Section: Discussionsupporting
confidence: 77%
“…25,27 Our utilisation analysis supports recent work, suggesting that urinary findings are taken into account when considering kidney offers. 26 The strengths of this study are its size, national coverage, data completeness and minimal loss to follow-up. We were able to account for several potential confounders of the relationships in question, and our results were consistent across several outcomes and when using other categorisations of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation